2015
DOI: 10.1007/s10103-015-1829-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cervical lesions by multivariate analysis of diffuse reflectance spectra: a clinical study

Abstract: Diffuse reflectance (DR) spectroscopy is a non-invasive, real-time, and cost-effective tool for early detection of malignant changes in squamous epithelial tissues. The present study aims to evaluate the diagnostic power of diffuse reflectance spectroscopy for non-invasive discrimination of cervical lesions in vivo. A clinical trial was carried out on 48 sites in 34 patients by recording DR spectra using a point-monitoring device with white light illumination. The acquired data were analyzed and classified usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…49 .In fact, some studies have indicated that sampling normal-appearing regions of the cervix could increase HSIL detection by up to 30%. 50,51 However, punch biopsy of the human cervix is associated with the increased risk of bleeding and infection (as in all biopsies) and is typically performed without anesthesia, even though the frequency and duration of moderate to severe pain is high. 52 Unfortunately, topical anesthetics have proven ineffective in providing pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…49 .In fact, some studies have indicated that sampling normal-appearing regions of the cervix could increase HSIL detection by up to 30%. 50,51 However, punch biopsy of the human cervix is associated with the increased risk of bleeding and infection (as in all biopsies) and is typically performed without anesthesia, even though the frequency and duration of moderate to severe pain is high. 52 Unfortunately, topical anesthetics have proven ineffective in providing pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Prabitha et al. has utilized PCA and LDA on the DR spectra recorded in vivo from 34 patients and reported a sensitivity of 89% and specificity of 97% for discriminating high‐grade SIL from normal and 100% sensitivity and specificity for discriminating HSIL from LSIL .…”
Section: Introductionmentioning
confidence: 99%
“…Prabitha et al. has recently carried out a clinical study by recording the diffuse reflectance (DR) images of cervix at the oxygenated haemoglobin absorption peaks of 545 nm and 575 nm . It was observed that the reflectance image intensity ratio R545/R575 could non‐invasively discriminate healthy tissue from premalignant and malignant lesions in real‐time.…”
Section: Introductionmentioning
confidence: 99%
“…Such difference in spectra detected by an optical sensor can be used in order to identify neoplastic lesions of the cervical epithelium. DRS is an indirect optical technique and may require either fitting of measured spectra with multi-parametric models describing the realistic optical properties of tissue [ 24 ] or using an efficient classification algorithm of optical spectra for the detection of HSIL [ 25 26 ]. The propagation of light in a scattering medium is usually modeled by the Monte Carlo algorithm.…”
Section: Reviewmentioning
confidence: 99%